2015
DOI: 10.1001/jamaoto.2014.2785
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Cause of Sudden Hearing Loss

Abstract: An African American man in his 40s initially presented with a sudden-onset unilateral hearing loss with associated vertigo and tinnitus. His medical history was unremarkable, and he specifically had no history of any auditory or vestibular symptoms. Results from his physical examination were also unremarkable and demonstrated normal otoscopic and neurologic findings. Audiometry results revealed a moderate right-sided sensorineural hearing loss across all frequencies (250-8000 Hz). Prior audiograms were unavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…methylprednisolone is used for a few days [Hoitsma et al, 2010;Jardine et al, 2015;Loor et al, 2012;Rose et al, 2014;Zajicek et al, 1999]. In many cases, patients experience stable, improved, or even complete resolution of disease although they may require long term corticosteroids [Carlson et al, 2015;Jardine et al, 2015;Loor et al, 2012].…”
Section: Etiology/pathophysiologymentioning
confidence: 99%
“…methylprednisolone is used for a few days [Hoitsma et al, 2010;Jardine et al, 2015;Loor et al, 2012;Rose et al, 2014;Zajicek et al, 1999]. In many cases, patients experience stable, improved, or even complete resolution of disease although they may require long term corticosteroids [Carlson et al, 2015;Jardine et al, 2015;Loor et al, 2012].…”
Section: Etiology/pathophysiologymentioning
confidence: 99%
“…In a review of the literature, Colvin [2006] reported 50 cases. Since then, fewer than 30 adult and pediatric cases have been referenced in PubMed [Colvin, Color version available online DOI: 10.1159/000514479 2006; Agari et al, 2007;Cama et al, 2011;Loor et al, 2012;Szmulewicz, and Waterston, 2012;Dhanjal et al, 2014;Rose et al, 2014;Jardine et al, 2015;Shimizu et al, 2016;Greene et al, 2017;Svrakic et al, 2017;Taous et al, 2017]. In most cases, hearing loss was mild to moderate and reversible after corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 305 patients diagnosed with neurosarcoidosis, Carlson et al [2014] reported that an optic neuropathy is the most prevalent cranial nerve lesion (30%) followed by trigeminal, facial, and audiovestibular nerve involvement (19, 18, and 17%, respectively). Audiovestibular manifestations are therefore relatively rare in sarcoidosis and have been described in a number of case reports [Colvin, 2006;Agari et al, 2007;Cama et al, 2011;Loor et al, 2012;Szmulewicz and Waterston, 2012;Dhanjal et al, 2014;Rose et al, 2014;Jardine et al, 2015;Shimizu et al, 2016;Greene et al, 2017;Svrakic et al, 2017;Taous et al, 2017]. The typical symptom is a mild to moderate sensorineural hearing loss usually bilateral (75%) and asymmetric (75%), slowly or rapidly progressive, sudden or fluctuating, and usually associated with signs of vestibular impairment [Colvin, 2006;Carlson et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of balance problems may be spontaneous or with medication while at least partial healing in the auditory functions is observed with high dose steroid treatment. 6,7 Here in this case report, a female patient with paresthezia in the left face half who afterwards experienced sudden hearing loss twice on the same side in only a week and responded to steroid treatment, diagnosed with possible NS will be presented. Written informed consent was obtained from patient who participated in this study.…”
Section: A Rare Cause Of Sudden Hearing Loss: Neurosarcoidosismentioning
confidence: 97%